2011
DOI: 10.1111/j.1464-5491.2011.03368.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with continuous glucose monitoring in adults and youths with Type 1 diabetes

Abstract: As frequent use of continuous glucose monitoring is associated with improved glycaemic control without increased hypoglycaemia it is important to overcome barriers, reinforce benefits and set realistic expectations for this technology in order to promote its more consistent and frequent use in individuals with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 8 publications
(2 reference statements)
9
113
0
1
Order By: Relevance
“…To maintain a high frequency of use, patients and their parents require in-depth training with reinforcement, including periodic follow-up with clinicians and diabetes educators. The results of the JDRF CGM Study Group, using all the first-generation CGM devices available at that time (2007), showed that (83). DirecNet studied the efficacy and safety of CGM in children <10 years of age.…”
Section: Pediatric Patients With T1dmmentioning
confidence: 99%
“…To maintain a high frequency of use, patients and their parents require in-depth training with reinforcement, including periodic follow-up with clinicians and diabetes educators. The results of the JDRF CGM Study Group, using all the first-generation CGM devices available at that time (2007), showed that (83). DirecNet studied the efficacy and safety of CGM in children <10 years of age.…”
Section: Pediatric Patients With T1dmmentioning
confidence: 99%
“…44 Many factors are associated with likehood of discontinuing technology use, including more severe hypoglycemic events after starting the pump, 44 physical discomfort of wearing the CGM, 12 difficulty with insertion/adhesives/sensor functioning, frequency of alarms, skin reactions to sensors, and interference with physical activity. 12,45 Parents and their adolescents may perceive different reasons for nonuse; in one major CGM clinical trial, parents believed that their adolescents resisted using CGM due to body image concerns, but youth attributed nonuse to practical issues such as insertion pain and frequent alarms. 13 High-frequency CGM users perceive fewer hassles to using the technology than low users.…”
Section: Barriers and Discontinuation Of Technology Usementioning
confidence: 99%
“…54 Positive user feedback for CGM includes being able to see trends in BG levels, being able to detect hypoglycemia more easily, and being able to correct out-of-range numbers. 45 Adolescents (versus other groups) do worse on CGM-they use it less, are less satisfied, are less accepting of hassles and burdens, and are less likely to meet A1c targets. 13 An exploratory study with cross-sectional data found greater parent-reported depression among children and adolescents using CGM compared to those using standard blood glucose monitoring, although adults using CGM reported less trait anxiety compared to the standard group.…”
Section: Technology Use and Psychosocial Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Naranjo et al reported in 2016 that those using pumps, CGMs, or sensor augmented pumps had more positive attitudes about diabetes technology than those on multiple daily injections and conventional glucose monitoring. 52 Among all participants in the JDRF CGM study group common barriers to continued use include insertion pain, system alarms, and body issues related to the need to wear the device, 53 although this was with early generation systems.…”
Section: Special Considerations In Pediatricsmentioning
confidence: 99%